Centenáriumi kalendárium - Béres, Zsuzsa (Gerundium, 2013)
A CENTENARY CALENDAR. In the previous issue of our periodical the proceedings of the Opening Event of the Series of Centenary Programmes of the University of Debrecen were given a detailed presentation. he current assortment ofers a chronological introduction of the most important university events of the Centenary Year of 2012. he calendar can make mention of a wide selection of respective programme events: in addition to various festive commemorations, exhibitions and conferences there is a salutation of the university’s irst Olympic champion, further sports and festival events are also mentioned.